Analisis Pendapatan Petani Nanas di Desa Lakologou, Kecamatan Tongkuno, Kabupaten Muna - Rosliyana; Mukhammad Idrus; Nur Afiah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research aims to analyze the income of pineapple farmers in Lakologou Village, Tongkuno Subdistrict, Muna Regency. Pineapple farming has good economic potential but is vulnerable to market price fluctuations and production cost factors. This study was conducted using a quantitative method through interviews and documentation, focusing on the income variable. The results show that pineapple farmers in this area earn an average income of IDR 19,478,641 per planting season from approximately 1.5 hectares of land. Total revenue reaches IDR 23,401,724 with total production costs of IDR 3,923,083. Farmer income is influenced by land area, selling prices, and production costs, all closely related to the farming feasibility. Based on the feasibility analysis, with an R/C ratio of 5.96, pineapple farming in Lakologou Village is deemed feasible and profitable. With proper management, this business holds great potential for further development to improve the welfare of local farmers.